MENGURANGI BIAS DAN MENINGKATKAN KESADARAN KEUANGAN PADA SISWA SMKN 15 JAKARTA - Ferdy Audrian Wibisono; Firda Melani Setiawan; Razyka Imayda; Ardhiani Fadila; Sri Mulyantini (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
This educational socialization activity aims to increase understanding of financial behavior bias among students at SMKN 15 Jakarta. The material provided is related to the types of financial bias, namely Representativeness Bias, Confirmation Bias, Sunk Cost Fallacy, Anchoring Effect, and Herding Mentality. This material is given in order to reduce financial behavioral biases in financial decision-making that occur in many students of SMKN 15 Jakarta, such as Representativeness Bias, Confirmation Bias, Sunk Cost Fallacy, Anchoring Effect, and Herding Mentality. Methods are provided through observation, educational socialization, discussion, quizzes through Quizizz, and feedback evaluation through Google Form. The results of this activity showed that the students participated in the implementation of Quizizz and answered enthusiastically. The results of the quiz showed that there was an increase in understanding related to financial bias. Partners expect the continuation of this activity in the future with additional materials